Botany, Pharmacognosy, and Phytochemical Study of Gymnanthemum amygdalina (Delile) Sch.Bip. Leaves from Bandung, West Java, Indonesia - Anindita, Reza; Tahapary, Manuela Esterlita; Nathalia, Dede Dwi; Putri, Intan Kurnia; Beandrade, Maya Uzia (Universitas Pattimura, 2025)
Gymnanthemum amygdalina (Delile) Sch.Bip. possesses antioxidant, antibacterial, anticholesterol, anticancer, and antidiabetic properties. This study aimed to determine the morphology of leaves, stems, flowers, and roots, as well as the microscopic powder characteristics, phytochemical profile, and Thin Layer Chromatography (TLC) pattern of G. amygdalina leaves. The samples were collected from Bandung City, West Java, Indonesia. Methods included morphological examination, microscopic powder analysis, phytochemical screening, and TLC. The morphological characterization of G. amygdalina showed that the leaves measured 10–22 cm in length and 2–8 cm in width, with an oblong shape, acuminate tips, acute bases, pinnate venation, serrated margins, rough surfaces, woody stems, and a taproot system. Microscopic examination revealed fragments of trichomes. Phytochemical screening indicated the presence of alkaloids, flavonoids, saponins, tannins, and terpenoids/steroids. TLC analysis showed five red spots with an average Rf value ranging from 0.06 to 0.58. In conclusion, the morphological characteristics of G. amygdalina leaves were identified, microscopic analysis revealed trichome fragments, and phytochemical screening confirmed the presence of secondary metabolites. TLC analysis yielded Rf values between 0.06 and 0.58.